Statistical Analysis of Genomic in-silico Pathogenicity Predictors - Aydin, Eylul; Ergun, Berk; Ng, Ozden Hatirnaz; Ozdemir, Ozkan (SPRINGERNATURE, 2024)
56th Annual Conference of the European-Society-of-Human-Genetics (ESHG), Glasgow, SCOTLAND, JUN 10-13, 2023